Greenhouse study and interviews indicate glyphosate residue via feed-feces-fertilizer route is a risk for horticultural producers using manure-based fertilizer - Birge, Traci; Saloniemi, Irma; Saikkonen, Kari; Helander, Marjo (SPRINGER, 2025)
Background: The herbicide glyphosate is the most widely used active ingredient in pesticides globally. Residues have been found in people, livestock, food and animal feed, and in the environment, but little is known about glyphosate residue in manure-based fertilizer. We describe a feed-feces-fertilizer route of glyphosate contamination with negative impacts for horticultural production. This exposure can harm sensitive plants, such as tomato, and pose a risk to effective waste disposal and nutrient cycling along principles of the circular economy. We review the use and history of glyphosate and present a mixed methods research based on a real-world case from Finland where glyphosate residue in poultry manure fertilizer was suspected of inhibiting commercial organic tomato production. To test the fertilizer, we grew 72 ‘Encore’ variety tomato plants for 14 weeks in a climate-controlled greenhouse according to the practices of the commercial grower. To ascertain awareness and potential contamination mitigation measures, we contacted five fertilizer companies with sales of biogenic fertilizer in Finland, two farming organizations, a feed company, and two government organizations working on nutrient cycling and agricultural circular economy.
Results: The total harvest of tomatoes grown with fertilizer with the higher content of glyphosate residue was 35% smaller and the yield of first-class tomatoes 37% lower than that of the control, with lower glyphosate concentration. Two of the five fertilizer companies identified poultry manure as a source of glyphosate contamination. Companies with awareness of pesticide residues reported interest in establishing parameters for pesticide residues.
Conclusions: The extent of glyphosate contamination of recycled fertilizers is unknown, but this study shows that such contamination occurs with negative impacts on crop production. Lack of testing and regulation to ensure that recycled fertilizers are free from harmful levels of glyphosate or other pesticides creates risks for agricultural producers. The issue is particularly acute for certified organic producers dependent on these products, but also for sustainable transitions away from mineral fertilizers in conventional farming. The example from Finland shows that a model of co-production between fertilizer producers and state regulatory agencies to establish safe limits can benefit both fertilizer producers and their customers. © The Author(s) 2024.